Lesion distribution in cases of canine atopic dermatitis in South Australia. Issue 8 (17th June 2019) - Graham, M; Chan, WY; Hill, P
Abstract : Objective: To determine the lesion distribution patterns in different breeds of dogs affected by atopic dermatitis in South Australia. Methods: The presence or absence of erythematous skin lesions in 267 cases of canine atopic dermatitis (CAD) was recorded across 36 anatomical sites. Breeds represented by ≥ 9 dogs were included in the analysis. The percentage of dogs showing lesions at each of the body sites was calculated and illustrated on colour‐coded diagrams. Variations in affected body sites within and between breeds were compared using Kruskal‐Wallis ANOVA and Dunn's multiple comparison tests. Results: The prevalence of skin lesions at different body sites differed significantly both in the population as a whole and within breeds. The sites affected in ≥ 75% dogs were the dorsal and ventral aspects of the front and hind paws. The sites affected in 50–74% were the medial pinnae, axillae, ventral chest, abdomen and perineum. Sites affected in 25–49% of dogs included the face, periocular region and forelimb. Remaining body sites were affected in < 25% of dogs. Analysis at the breed level revealed some differences from this standard distribution pattern. Conclusion: The results of this study confirmed the typical lesion distributions seen in CAD and highlighted some subtle differences in breeds commonly seen in South Australia. This will be useful for clinical practitioners in prioritising differential diagnoses for pruritic skin conditions.